Role of Local Fields in Interionic Interactions on Atomic Transport Properties of Liquids Ti, Mn, and Pt (Bangladesh Journal of Physics, 2024)
Temperature-dependent atomic transport properties, namely diffusion coefficient (D) and shear viscosity coefficient (η) of liquids Ti, Mn, and Pt, have been studied utilizing the Brettonet-Silbert (BS) pseudopotential with five different local field correction functions (LFCFs). The liquid structure is determined by both Variational modified Hypernetted Chain (VMHNC) integral equation theory and the Linearized Week-Chandler-Andersen (LWCA) perturbation method, which provides an acceptable pair correlation function, g(r), through the above-mentioned potential of the concerned LFCFs. Then g(r) is linked to the universal scaling laws (USLs) of Rosenfeld, Dzugutov, and Li to determine D and η. The results show that D increases, and η decreases with increasing temperature, as expected. D obtained using the LFCF of Sarker et. al. (S) provides excellent results for liquids Mn and Pt, while that of Taylor et al. (T) works well for liquid Ti. In the case of η, the LFCF of Sarker et. al. (S) works reasonably well compared to the available theoretical value and experimental data than any other LFCFs for all concerned systems.Bangladesh Journal of Physics, Vol. 31, Issue 2, pp. 83 – 105, December 2024